2015
DOI: 10.1093/ije/dyu276
|View full text |Cite
|
Sign up to set email alerts
|

High tobacco consumption lowers body weight: a Mendelian randomization study of the Copenhagen General Population Study

Abstract: High tobacco consumption causes lower body weight among current smokers. However, smoking does not seem to affect body shape or fat distribution causally. The lack of association between CHRNA3 genotype and body weight among former smokers and never smokers favours smoking as the causal factor for the observed associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 40 publications
3
48
3
Order By: Relevance
“…In a similar manner, [22] demonstrates that the smoking heaviness-increasing allele of rs16969968 is associated with lower body mass index in current and former smokers but not in never-smokers , suggesting that heavier smoking causally lowers body weight. The finding has been replicated and extended to other measures of adiposity (e.g., waist circumference) in subsequent MR analyses 23, 24, 25. Similar analyses have shown that smoking leads to higher resting heart rate and may adversely affect kidney function, as it leads to higher estimated glomerular filtration rate 25, 26, as well as all-cause mortality [27].…”
Section: Causal Analyses and Mendelian Randomisation (Mr)mentioning
confidence: 61%
“…In a similar manner, [22] demonstrates that the smoking heaviness-increasing allele of rs16969968 is associated with lower body mass index in current and former smokers but not in never-smokers , suggesting that heavier smoking causally lowers body weight. The finding has been replicated and extended to other measures of adiposity (e.g., waist circumference) in subsequent MR analyses 23, 24, 25. Similar analyses have shown that smoking leads to higher resting heart rate and may adversely affect kidney function, as it leads to higher estimated glomerular filtration rate 25, 26, as well as all-cause mortality [27].…”
Section: Causal Analyses and Mendelian Randomisation (Mr)mentioning
confidence: 61%
“…As BMI-related transitions to poor health and death may differ by sex, we repeated analyses including interactions between sex and BMI in the multinomial logistic models. Finally, since tobacco smoking is associated with increased risk of mortality and morbidity 33, 34 and it is also typically associated with lower weight, 35 we conducted sensitivity analyses among never smokers using a bootstrap method with 50 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…The MR GxE approach has been used to investigate the effect of smoking heaviness on traits such as body mass index (BMI) and depression/anxiety (1520). A causal effect of a genetic variant known to affect smoking heaviness should, if the effect is solely via tobacco intake, be seen in participants who are previous or current smokers, but not in participants who have never smoked.…”
Section: Introductionmentioning
confidence: 99%